2017
DOI: 10.4269/ajtmh.16-0955
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Introducing Malaria Rapid Diagnostic Tests on Fever Case Management: A Synthesis of Ten Studies from the ACT Consortium

Abstract: Abstract.Since 2010, the World Health Organization has been recommending that all suspected cases of malaria be confirmed with parasite-based diagnosis before treatment. These guidelines represent a paradigm shift away from presumptive antimalarial treatment of fever. Malaria rapid diagnostic tests (mRDTs) are central to implementing this policy, intended to target artemisinin-based combination therapies (ACT) to patients with confirmed malaria and to improve management of patients with nonmalarial fevers. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 55 publications
(38 reference statements)
1
50
0
Order By: Relevance
“…8 Médecins Sans Frontières, Geneva, Switzerland. 9 Médecins Sans Frontières -Manson Unit, London, UK. 10 Médecins Sans Frontières, Barcelona, Spain.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Médecins Sans Frontières, Geneva, Switzerland. 9 Médecins Sans Frontières -Manson Unit, London, UK. 10 Médecins Sans Frontières, Barcelona, Spain.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…As a result of increased malaria elimination efforts and the subsequent worldwide decline in malaria cases, clinicians in LMICs are now encountering an increasing number of malaria rapid diagnostic test (RDT)-negative febrile patients and/or malaria RDT-positive febrile patients who are co-infected with both Plasmodium as well as another fever-inducing pathogen [8][9][10][11]. To date, in LMICs, beyond the use of a malaria RDT and/or microscopy for some locations [12], no aetiology-based diagnostic test is currently employed or recommended by the World Health Organization (WHO) for any other fever-inducing pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one investigative team had a broad enough perspective to look beyond the narrow focus of the investigation protocol itself and identified unintended consequences of a well-conceived public health intervention. 6 The reality of application may differ Severe malaria manifested as shock and lactic acidosis much more commonly than severe anemia. Severe malaria had age peaks at 2-3 years and in those older than 50 years.…”
Section: Natural Selectionsmentioning
confidence: 99%
“…Severe malaria had age peaks at 2-3 years and in those older than 50 years. Bruxvoort et al 6 Effect of diagnostics on management Rapid tests improved appropriate treatment with artemisinin combination therapy for test-positive and negative cases, but many cases were not treated according to test results. Cash-Goldwater et al 11 Infection risk factors Brucellosis confirmed by blood culture, or 4-fold rise in microagglutination was confirmed or probable in 9% of febrile patients, mostly who attend animals but were not suspected by medical providers.…”
Section: Natural Selectionsmentioning
confidence: 99%
See 1 more Smart Citation